2023
DOI: 10.1139/cjfas-2022-0076
|View full text |Cite
|
Sign up to set email alerts
|

Tributary streams provide migratory fish with access to floodplain habitats in a regulated river: evidence from alligator gar, Atractosteus spatula

Abstract: Migratory fishes with periodic life history strategies are sensitive to river regulation. Populations of these fishes may persist in highly regulated rivers by using tributaries that provide access to intermittently connected spawning and early life stage habitat in floodplains. We analyzed system hydrology and associated movement of a long-lived periodic strategist, the alligator gar (Atractosteus spatula), in the Brazos River, Texas. We hypothesized that: 1) flow regulation on the mainstem has resulted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Tributaries also can provide habitat conditions that have been lost in contemporary mainstem rivers (i.e., vestige large river habitats) due to regulation or channelization. For example, alligator gar (Atractosteus spatula) in the regulated Brazos and Arkansas rivers make predictable seasonal movements into freeflowing tributaries to access inundated floodplains as discharge and water temperatures rise (Naus and Adams, 2018;Roberts et al, 2022). In the lower Missouri River, channelization and levees preclude low velocity, shallow habitat conditions within the mainstem; however, the lower reaches of tributaries often exhibit reduced velocities and shallower depths compared to the mainstem (Brown and Coon, 1994).…”
Section: Provisioning Of Portfolio Assets By Tributaries For Fish Pop...mentioning
confidence: 99%
See 1 more Smart Citation
“…Tributaries also can provide habitat conditions that have been lost in contemporary mainstem rivers (i.e., vestige large river habitats) due to regulation or channelization. For example, alligator gar (Atractosteus spatula) in the regulated Brazos and Arkansas rivers make predictable seasonal movements into freeflowing tributaries to access inundated floodplains as discharge and water temperatures rise (Naus and Adams, 2018;Roberts et al, 2022). In the lower Missouri River, channelization and levees preclude low velocity, shallow habitat conditions within the mainstem; however, the lower reaches of tributaries often exhibit reduced velocities and shallower depths compared to the mainstem (Brown and Coon, 1994).…”
Section: Provisioning Of Portfolio Assets By Tributaries For Fish Pop...mentioning
confidence: 99%
“…Thus, the value of a tributary likely depends on the ability of tributaries to provide habitats that fulfill specific life-history functions of mainstem fishes. Small tributaries within floodplain rivers can provide offchannel, low-velocity habitats, Brown and Coon, 1994;Bottcher et al, 2013;Naus and Adams, 2018;Phillis et al, 2018) and vital conduits to backwater habitats (Roberts et al, 2022). Further, small tributaries may contribute to invertebrate and allochthonous inputs to mainstem regulated rivers (Whiting et al, 2014;Sabo et al, 2018;Milner et al, 2019), which can be food limited given extensive alteration (Cross et al, 2013).…”
Section: Future Research Areas To Advance Understanding Of the Roles ...mentioning
confidence: 99%
“…Numerous studies on Alligator Gar movement provide evidence of their preferential use of different habitats relative to seasonal patterns and flow conditions [8,10,15,[18][19][20][21][22][23]. Allen et al [15], Buckmeier et al [20], and Kluender et al [22] reported the least amount of movement during the cooler winter season and increased movement relative to warmer temperatures and higher water levels associated with their spawning season.…”
Section: Introductionmentioning
confidence: 99%
“…Allen et al [15], Buckmeier et al [20], and Kluender et al [22] reported the least amount of movement during the cooler winter season and increased movement relative to warmer temperatures and higher water levels associated with their spawning season. In riverine settings, reproductive migrations of Alligator Gar included two distinct macrohabitats off the main channel, inundated floodplains [10,15,20,22,23] and tributaries [18,22,23]. Data from these studies, and others, help constrain known factors that influence floodplain spawning behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation